(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
Culture is one of the interesting and important exploratory studies to study. One of the cultural elements that can be studied through a mathematical approach is the Kempul, Suwukan, and Gong musical instruments in Javanese gamelan. The purpose of this research is to find out: (1) the history and philosophy of Kempul, Suwukan, and Gong and (2) the fundamental activities according to Bishop in Kempul, Suwukan and Gong. This study uses a qualitative approach with an ethnographic approach, which describes the musical instruments Kempul, Suwukan, and Gong as a medium for learning mathematics. The resource persons in this study were the supervisors and administrators of the Karawitan UKM at Sanata Dharma University. Data collection techniques used are observation, interviews, and documentation. The instrument of this research is the human instrument. The results of this study found mathematical concepts in Kempul, Suwukan, and Gong musical instruments based on the study of fundamental activities according to Bishop. Mathematical concepts in Kempul, Suwukan, and Gong include relations, equations of circles, three-dimensional geometry in the form of tubes and half spheres, and integral calculus especially on the volume of rotating objects using the disc method.